2020
DOI: 10.1080/17451000.2020.1711952
|View full text |Cite
|
Sign up to set email alerts
|

Cophylogenetic analysis of the relationship between anemonefish Amphiprion (Perciformes: Pomacentridae) and their symbiotic host anemones (Anthozoa: Actiniaria)

Abstract: Last but not least, I wish to express my deepest gratitude for my family: my mom, my dad, who took care my little daughter during three years of my research and study. They sacrificed their happiness for my happiness, their days for my days. I would like to thank for my sisters and my brother for your effort to look after my daughter during my absence. Above all, I would express my special thanks to my husband Cao D.V and my daughters, Lan Chi and Bao An, for your endless love, understanding and support. You a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 84 publications
(95 reference statements)
6
16
0
Order By: Relevance
“…16.476524 doi: bioRxiv preprint anemonefishes with 100 % bootstrap support (Figure 4 and Figure S2). This topology has only been reported in two other studies that used mitochondrial genes to reconstruct anemonefish phylogenies [81,82]. Pomacentrids (and anemonefishes in particular) have long been a challenge in systematics due to their high diversity and intraspecific variation [83], therefore discordances in our tree may also stem from insufficient information (i.e., only 11 out of the 28 described species were used).…”
Section: Phylogenetic Analysismentioning
confidence: 73%
“…16.476524 doi: bioRxiv preprint anemonefishes with 100 % bootstrap support (Figure 4 and Figure S2). This topology has only been reported in two other studies that used mitochondrial genes to reconstruct anemonefish phylogenies [81,82]. Pomacentrids (and anemonefishes in particular) have long been a challenge in systematics due to their high diversity and intraspecific variation [83], therefore discordances in our tree may also stem from insufficient information (i.e., only 11 out of the 28 described species were used).…”
Section: Phylogenetic Analysismentioning
confidence: 73%
“…Symbiotic relationships affect the host in different ways (positively, neutrally, or negatively) and are the key drivers of ecological function and evolutionary processes (Fisher et al, 2017). A large body of research has documented that extended inter species relationships can often, but not always, lead to co-evolution (Song et al, 2015;Fountain et al, 2017;Pollock et al, 2018;Nguyen et al, 2020). The relationships between decapod hosts and species within Octolasmis appears to be a facultative rather than an obligatory association (Fernandez-Leborans, 2010), and there exists a large gap in our knowledge about population dynamics, and the driving forces leading to the relationships.…”
Section: Symbiont Infestation and Host Distributionmentioning
confidence: 99%
“…Second, there is a complex species-specificity of this mutualistic relationship between fish and the 10 possible sea anemone hosts, which is probably related to the toxicity levels of the hosts [21]. Recent data have shown that the giant sea anemones that host anemonefish form three independent distantly related groups and that their taxonomy is still unclear [22,23]. This allows to conclude that, in contrast to anemonefish for which the symbiosis has been established once [4], on the sea anemone side the symbiosis has evolved independently at least three times.…”
Section: Symbiotic Relationshipmentioning
confidence: 99%
“…It has been shown that this symbiotic interaction has been critical for the evolutionary radiation of anemonefish [ 3 , 4 ]. In contrast, the diversification of giant sea anemones predates the symbiosis [ 22 , 23 ]. The taxonomy of the sea anemones is far from settled and will be important to better understand this complex relationship.…”
Section: Major Interests and Research Questionsmentioning
confidence: 99%